BAHASA, VARIETAS BAHASA, DAN VARIABEL-VARIABEL PENENTU PENGGUNAANNYA. - I Nyoman Adi Jaya Putra (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2010)
Almost every language has its own varieties. In any verbal interaction, the use of certain varietiesis determined by such social variables as social status, age, sex, and education. Besides these socialvariables, there are also affecting factors such as psychological factor of the participant, geographicalfactor, and socio-cultural factor of a speech community. While communicating, a speaker uses acertain variety of a language in order to show his relative position or his relationship with his interlocutor.No single strategy is associated with the use of a certain variety of a language—whichevervariety is used merely exhibits a speaker’s verbal repertoire which accordingly could be activated indifferent speech events, with different objectives, as well as with different illocutionary force.